Forecasting seizure clusters from chronic ambulatory electrocorticography - Ilyas, Adeel; Hoffman, Clarissa; Vakilna, Yash; Chaliyeduth, Sreekanth; Muhlhofer, Wolfgang; Riley, Kristen O.; Dabaghian, Yuri; Lhatoo, Samden D.; Pati, Sandipan (Epilepsia (Copenhagen), 2022)
Seizure clusters are seizures that occur in rapid succession during periods of heightened seizure risk and are associated with substantial morbidity and sudden unexpected death in epilepsy. The objective of this feasibility study was to evaluate the performance of a novel seizure cluster forecasting algorithm. Chronic ambulatory electrocorticography recorded over an average of 38 months in 10 subjects with drug‐resistant epilepsies was analyzed pseudoprospectively by dividing data into training (first 85%) and validation periods. For each subject, the probability of seizure clustering, derived from the Kolmogorov–Smirnov statistic using a novel algorithm, was forecasted in the validation period using individualized autoregressive models that were optimized from training data. The primary outcome of this study was the mean absolute scaled error (MASE) of 1‐day horizon forecasts. From 10 subjects, 394 ± 142 (mean ± SD) electrocorticography‐based seizure events were extracted for analysis, representing a span of 38 ± 27 months of recording. MASE across all subjects was .74 ± .09, .78 ± .09, and .83 ± .07 at .5‐, 1‐, and 2‐day horizons. The feasibility study demonstrates that seizure clusters are quasiperiodic and can be forecasted to clinically meaningful horizons. Pending validation in larger cohorts, the forecasting approach described herein may herald chronotherapy during imminent heightened seizure vulnerability.